2000
DOI: 10.1177/01461672002610006
|View full text |Cite
|
Sign up to set email alerts
|

Memory Bias in Long-Term Close Relationships: Consistency or Improvement?

Abstract: How do partners in long-term relationships construct memories of the past? The current study examined 20 years of retrospective and longitudinal data from a sample of wives to evaluate two possible answers to this question. Findings indicate that wives invoke different theories of the past at different stages of life. At 10 years into the study, wives’ memories of the past were negatively biased, such that present ratings seemed a significant improvement. At 20 years into the study, wives’ memories of the past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 36 publications
6
86
0
1
Order By: Relevance
“…Previous longitudinal studies have found that couples sometimes distort past memories to be consistent with a perception that their relationships are improving over time (Frye & Karney, 2004;Karney & Coombs, 2000). This might lead to a prediction that people will remember recent conflicts as being the more positive (and less negative) than distant conflicts, but, in contrast to such a prediction, the present study found no significant correlations between these variables for wives and small bivariate correlations in the opposite direction for husbands (recent memories were more negative and less positive).…”
Section: Discussionmentioning
confidence: 98%
“…Previous longitudinal studies have found that couples sometimes distort past memories to be consistent with a perception that their relationships are improving over time (Frye & Karney, 2004;Karney & Coombs, 2000). This might lead to a prediction that people will remember recent conflicts as being the more positive (and less negative) than distant conflicts, but, in contrast to such a prediction, the present study found no significant correlations between these variables for wives and small bivariate correlations in the opposite direction for husbands (recent memories were more negative and less positive).…”
Section: Discussionmentioning
confidence: 98%
“…The study program completers recalled their initial competency ratings as worse than they really were-creating an illusion of improvement. Similarly, Karney and Coombs (2000) found an illusion of improvement in people's assessments of their marriages. A sample of wives rated emotional aspects of their marriage initially at time 1 and then again at times 2 and 3, 10 and 20 years later, respectively.…”
Section: Biased Remembering Of Our Past Selvesmentioning
confidence: 97%
“…For example, researchers have shown that self-enhancement and self-protection (Sanitioso et al, 1990;Sedikides et al, 2004;, relational and belongingness needs (Gardner, Pickett, & Brewer, 2000;Karney and Coombs, 2000), communication goals (Echteroff, Higgins, Kopietz, & Groll, 2008), and agency and communion motivation (Woike, Lavezzary, & Barsky, 2001) can lead to memory reconstruction and selective memory biases. Sanitioso et al (1990), for example, found that participants who learned that introversion was related to academic success subsequently recalled more autobiographical instances of introverted behaviors than extroverted behaviors.…”
Section: Outcome Motivation and Memory Biasmentioning
confidence: 99%